Influence of hemp shiv, cement, and water content on the properties of lightweight hemp composites produced using different sizes of hemp shiv - Sahin, Murat (Revista de la Construcción. Journal of Construction, 2023)
This study investigated the production and properties of lightweight hemp composites produced using waste industrial hemp stems cultivated in Turkey. Hemp stems were separated from their fibers and fragmented to obtain hemp shiv aggregates in the laboratory. Twelve mixtures were prepared with varied volumetric ratios of hemp: cement (H:C) and hemp: water (H: W) using different sizes of hemp shiv. The influence of mix proportions on the physical and mechanical properties of hemp composites were investigated. Besides, microstructure of hemp composites was examined. The hemp composites produced were in the apparent density range of 312 to 928 kg/m3 and exhibited 0.20 to 1.24 MPa compressive strength. The water absorptions of samples were in the range of 3.47 and 8.50 kg/m2.h1/2. The apparent density and compressive strength of hemp composites decreased with the increase of H:C ratio, but this situation is the opposite for increase of H: W ratio and hemp shiv size. Besides, increase in H:C ratio or hemp shiv size caused higher water absorptions.